Angiogenesis in Cancers - Ribatti, Domenico (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Tumor progression is linked to a switch in the balance between positive and negative regulators, and mainly depends on the release by inflammatory or neoplastic cells of specific growth factors. Inflammatory infiltration contributes to tumor progression and metastatic process, and there are many reports of associations between tumor inflammatory infiltration, progression and prognosis. New therapeutic approaches have been developed with the aim to control tumor progression through the targeting of different components of the tumor microenvironment. This reprint will be useful for anyone who wants to learn about cancer: professors and students at universities, scientists at research institutes, biotechnology, and pharmaceutical labs, and lawyers trying to understand the patent literature.